A review of benchmarking in carbon labelling schemes for building materials - Wu, Peng; Feng, Y.; Pienaar, J.; Xia, B. (Elsevier Ltd, 2014)
© 2015 Elsevier Ltd. As one of the largest sources of greenhouse gas (GHG) emissions, the building and construction sector is facing increasing pressure to reduce its life cycle GHG emissions. One central issue in striving towards reduced carbon emissions in the building and construction sector is to develop a practical and meaningful yardstick to assess and communicate GHG results through carbon labelling. The idea of carbon labelling schemes for building materials is to trigger a transition to a low carbon future by switching consumer-purchasing habits to low-carbon alternatives. As such, failing to change purchasing pattern and behaviour can be disastrous to carbon labelling schemes. One useful tool to assist customers to change their purchasing behaviour is benchmarking, which has been very commonly used in ecolabelling schemes.This paper analyses the definition and scope of benchmarking in the carbon labelling schemes for building materials. The benchmarking process has been examined within the context of carbon labelling. Four practical issues for the successful implementation of benchmarking, including the availability of benchmarks and databases, the usefulness of different types of benchmarks and the selection of labelling practices have also been clarified.